2016
DOI: 10.1051/parasite/2016067
|View full text |Cite
|
Sign up to set email alerts
|

A description ofEchinorhynchus baeriKostylew, 1928 (Acanthocephala: Echinorhynchidae) fromSalmo truttain Turkey, with notes on synonymy, geographical origins, geological history, molecular profile, and X-ray microanalysis

Abstract: A population of Echinorhynchus baeri Kostylew, 1928 with 18–24 rows of 8–10 proboscis hooks each and long fusiform eggs measuring 95–110 × 18–22 μm collected from Salmo trutta (Salmonidae) in a branch of the Murat River in Turkey is described and specimens are designated as neotype. Specimens of two similar populations of E. baeri (E. baeri Kostylew, 1928 and E. sevani Dinnik, 1932) were previously described from Salmo ischchan in Lake Sevan, Armenia. Waters of Lake Sevan and the Murat River were previously jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Results of the analysis of mineral content in proboscis hooks are found in Figure 24 and Table 4 . The metal profile of hooks has been reported previously for Echinorhynchus baeri Kostylew, 1928 [ 2 ] and Rhadinorhynchus oligospinosus Amin and Heckmann, 2017 [ 3 ], among other species of acanthocephalans. In N. peruensis , the magnesium (Mg) appeared in marked amounts.…”
Section: Resultsmentioning
confidence: 66%
“…Results of the analysis of mineral content in proboscis hooks are found in Figure 24 and Table 4 . The metal profile of hooks has been reported previously for Echinorhynchus baeri Kostylew, 1928 [ 2 ] and Rhadinorhynchus oligospinosus Amin and Heckmann, 2017 [ 3 ], among other species of acanthocephalans. In N. peruensis , the magnesium (Mg) appeared in marked amounts.…”
Section: Resultsmentioning
confidence: 66%
“…There is a difference in the distribution of calcium ions in the smaller hooks in relation to large hooks, this level being highest in the core and base of large hooks (45/30%) but highest at the tip of small hooks (30.57%) (Tables 3 and 4). A similar EDAX study of the proboscis hooks of Echinorhynchus baeri Kostylew, 1928 showed that large hooks have higher calcium, phosphorus, and sulfur than miniature rootless hooks [6]. Comparable patterns for the numerous trunk spine gallium cuts (Table 5) demonstrate the rigid nature of the spine which is explained by the X-ray scans (Fig.…”
Section: Discussionmentioning
confidence: 83%
“…This element along with calcium and phosphorus aid in the mineralization and hardening of the outer layer of hooks, similar to the enamel layer of the mammalian tooth (calcium phosphate apatite) [32]. The base center of large hooks shows increased levels of calcium (45.30%) and phosphate ions (14.87) (Table 3), comparable to the inner core of mammalian teeth [6]. Sulfur levelsshowed a higher differential concentration at the edge than the middle of cut hooks (Tables 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…Our results are comparable to those of mammalian teeth enamel. A similar EDAX study was carried out on the proboscis hooks of Echinorhynchus baeri Kostylew, 1928 showing that the large hooks have higher calcium, phosphorus, and sulfur than miniature rootless hooks [ 5 ]. Additional studies [ 15 , 16 , 37 ] have reported on hardened hooks and teeth enamel using elemental analysis (XEDs, EDAX).…”
Section: Resultsmentioning
confidence: 99%